The Economics of Warm Glow: A Note on Consumer's Behavior and Public Policy Implications - Paulo A.L.D. Nunes; Laura Onofri (Fondazione Eni Enrico Mattei (FEEM), 2004)
The paper focuses on the ongoing debate on non-market valuation, including the valuation environmental goods, and the opportunity to use contingent valuation for policy guidance. In fact, contingent valuation critics argue that reported willingness to pay answers do not reflect real economic preferences and, for this reason, should not be used in cost-benefit analysis The attempt to contravene such critique finds many supporters. This paper starts from the latter stream of research and adds two original contributions. First, it sheds light on the individual warm glow motivational profile, exploring the empirical relationship between individual's socio-economic characteristics and warm glow. Second, it discusses some implications of the presence of warm glow for public policy.
Keywords: D11; D12; Q26; 330; Economic value; Contingent valuation; Willingness to pay; Latent factor; Consumer motivations; Warm glow; Ego driven warm glow; Social oriented warm glow; Public policy design; Zahlungsbereitschaftsanalyse; Umweltschutz; Konsumentenverhalten; Altruismus; Schätzung; Portugal